Pengaruh Ekstrak Daun Teh terhadap Kualitas Motilitas Spermatozoa Mencit Jantan yang Diberi Paparan Asap Rokok - Meki Karolina; Edwin Lewis; Evelyn Angie; Sondang, Silitonga (PHARMANAJA : PHARMACEUTICAL JOURNAL OF UNAJA, 2023)
Background: Cigarette smoke exposure is a major contributor to male infertility due to its oxidative stress effects on spermatozoa. Tea leaf extract is known to contain high levels of antioxidants that may counteract these effects. Objective: To determine the effect of tea leaf extract on sperm motility quality in male mice exposed to cigarette smoke. Method: This experimental study used 24 male mice divided into four groups: negative control, cigarette smoke exposure, and two treatment groups receiving cigarette smoke exposure along with 200 mg/kg BW and 400 mg/kg BW of tea leaf extract. Sperm motility was assessed using microscopic examination after 14 days of treatment. Results: The group exposed to cigarette smoke alone showed significantly decreased sperm motility. Administration of tea leaf extract at both doses improved sperm motility, with the 400 mg/kg BW group showing a motility value close to the negative control. Conclusion: Tea leaf extract significantly improves sperm motility in mice exposed to cigarette smoke, likely due to its antioxidant content.